Treatment and Follow-Up of 22 Unruptured Wide-Necked Intracranial Aneurysms of the Internal Carotid Artery with Onyx HD 500 - Weber, Werner; Siekmann, Ralf; Kis, Bernhard; Kuehne, Dietmar (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: The purpose of this study was to demonstrate endovascular treatment of wide-necked aneurysms of the internal carotid artery with the liquid embolic agent Onyx HD 500.METHODS: Twenty-two wide-necked, large or giant aneurysms of the internal carotid artery (ICA) were treated in 22 patients with Onyx HD 500 (15 ophthalmic, 1 clinoid, and 6 cavernous aneurysms). Sixteen patients were asymptomatic, and mass effect of the aneuryms caused cranial nerve palsy in 6. Seven aneurysms showed regrowth after prior endovascular coiling.RESULTS: Postinterventional angiography demonstrated total occlusion in 18 aneurysms, and a small remnant was left in 4. Clinical and angiographic follow-up data are available in 19 patients (average follow-up, 13 months; range, 5–36 months). Total occlusion was demonstrated in 17 aneurysms (91%), and a partial recanalization was seen in 2. There were 2 ICA occlusions and 1 ICA stenosis. Clinical follow-up demonstrated a transient ischemic attack in 1 patient; 2 with cranial nerve palsy were unchanged, and 2 showed improved symptoms compared with the findings before treatment. The remaining 14 patients were clinically asymptomatic. There was no permanent severe morbidity and no mortality at follow-up.CONCLUSION: The endovascular treatment of wide-necked, large or giant ICA aneurysms with Onyx HD 500 is a treatment option in these selected cases. The benefit is a primary high and stable occlusion rate and good clinical outcome. ICA occlusion caused by Onyx migration in the parent artery is a typical problem, with a benign clinical course in this series.